SIMBOL-SIMBOL SATANISME DALAM PERSPEKTIF TEORI SIMBOL ERNST CASSIRER - Dewi, Yanti Kusuma (Jurnal Filsafat "WISDOM", 2009)
AbstractSatanism is known as a current satan worshipper. Term of satanism was officially introduced by Anton Szandor LaVey whoalso presented rituals with using symbols. Nowadays, satanismsymbols are more multifarious and used by the followers and the non-followers. In his theory of symbol, Ernst Cassirer said that symbol created of form which consist of language, myth, religion, art, science, and said that human has a conciousness to make a symbolic representation. The symbols in the satanism are Baphomet, inverse pentacle, goat of mendes, inverse cross, mano cornuto, sigil of lucifer, mano fico, and sulphur. The satanism symbols are organized from form (language, myth, art, and religion). Then, intuition function in satanism symbols gives an effect on cultural progress where the symbols are seen as accessories and non-satanism worshippers use those symbols without any comprehension of meaning.Keyword: Satanism, Symbols, Ernst Cassirer.